PANDAWA 5: INTERNALISASI NILAI MORAL DAN EDUKASI ANAK JALANAN MELALUI LEARN TO SHINE GUNA MEMBANGUN 21ST CENTURY SKILL - Mifdal Zusron Alfaqi Alfaqi; Abd. Mu’id Aris Shofa; Rista Ayu Mawarti; Zulfikar Waliyuddin Fattah; Rika Safitri Nur Azizah; Randy Tirto Buana; Laksamana Prammana Agung (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
Street Children are ironic evidence of the inequality of life, one of which is in the aspect of education. The existence of street children in the city of Malang continues to increase, in the last year there were 104 people. The existence of street children who do not have access to education is due to poor family economic factors, so they choose to drop out of school to work to meet their family's needs. There is a community that empowers street children in the city of Malang, namely Save Street Child this community provides educational services to street children but has not been able to develop moral character and 21st century skill competencies. This community service aims to build 21st century skills through internalization of moral values ​​and education that are integrated into the Pandawa 5 characters with a learn to shine approach. The implementation method for this community service activity was carried out on Sunday, June 11, 2024. There are 4 implementation methods used, namely 1) problem identification; 2) determination of community service objectives; 3) Preparation of operational design; 4) implementation and data collection; 5) data analysis; and 6) reporting and publication. The results of community service are able to improve the 21st century skill competency of street children in Malang city. Internalization of moral values ​​and education of street children in the 5 Pandawa figures through the learn to shine approach is able to provide religious morals, integrity, independence, nationalism, and mutual cooperation. In fact, this community service is an innovation in realizing proper educational access for street children in Malang city.